Influence of subclinical hypothyroidism on metabolic parameters in obese children and adolescents - Ozlem Kara (The Korean Pediatric Society, 2020)
Background Subclinical hypothyroidism (SH) is a common condition in obese children. However, its effect on glucose and lipid metabolism in obese children remains controversial. Purpose The present study aimed to investigate the association between SH and metabolic parameters. Methods A total of 215 obese children and adolescents aged 6-18 years were included in this retrospective cross-sectional study. The patients' anthropometric measurements such as thyrotropin (TSH), free thyroxine (fT4), fasting plasma glucose, and insulin levels, as well as homeostasis model assessment for insulin resistance (HOMA-IR) index, and lipid profiles were evaluated. The patients were allocated to the SH group (fT4 normal, TSH 5-10 mIU/L) (n=77) or the control group (fT4 normal, TSH<5 mIU/L) (n=138). The glucose and lipid metabolisms of the 2 groups were compared. Results SH was identified in 77 of 215 patients (36%). Mean body mass index was similar in both groups. The mean serum insulin, HOMA-IR, and triglyceride (TG) levels were higher and the mean high-density lipoprotein cholesterol level was lower in the SH group than in the control group (p=0.007, P=0.004, P=0.01, and P=0.02, respectively). A positive correlation was observed between TSH level and insulin level, HOMA-IR, and TG level. Conclusion SH was identified in some of the obese children and adolescents. A clear association was observed between SH, insulin resistance, and dyslipidemia in obese children.